Ascending aorta dilatation rates in patients with tricuspid and bicuspid aortic stenosis: the COFRASA/GENERAC study. (25th July 2017) - Kerneis, Caroline; Pasi, Nicoletta; Arangalage, Dimitri; Nguyen, Virginia; Mathieu, Tiffany; Verdonk, Constance; Codogno, Isabelle; Ou, Phalla; Duval, Xavier; Tubiana, Sarah; Cimadevilla, Claire; Vahanian, Alec; et al.
Abstract: Background: Ascending aorta (AA) dilatation is common in aortic valve stenosis (AS) but data regarding AA progression, its determinants and impact of valve anatomy [bicuspid (BAV), or tricuspid (TAV)] are scarce. Methods and Results: Asymptomatic AS patients enrolled in a prospective cohort (COFRASA/GENERAC) with at least 2 years of follow-up were considered in the present analysis. A transthoracic echocardiography (TTE) and a computed tomography (CT) scan were performed at inclusion and yearly thereafter. We enrolled 195 patients [mean gradient 22 ± 11 mmHg, 42 BAV patients (22%)]. Mean aorta diameters assessed using TTE were 35 ± 4 and 36 ± 5 mm at the sinuses of Valsalva and tubular level, respectively. Ascending aorta diameter was >40 mm in 29% of patients (24% in TAV vs. 52% in BAV, P  < 0.01). Determinants of AA diameters were age, sex, BSA, and BAV, but not AS severity. After a mean follow-up of 3.8 ± 1.5years, AA enlargement rate assessed using TTE was +0.18 ± 0.34 mm/year and +0.36 ± 0.54 mm/year at the Valsalva and tubular level, respectively. Determinants of the progression of AA size were smaller AA diameter ( P  < 0.01) but not baseline AS severity or valve anatomy (all P  > 0.05). Only four patients presented an AA progression ≥2 mm/year. Correlations between TTE and CT scan were excellent (all r >0.74) and similar results were obtained using CT. During follow-up, two BAV patients underwent a combined AA surgery; no surgery was primarily performed for AA aneurysm and no dissection was observed. Conclusion: In this prospective cohort of AS patients determinants of AA diameters were age, sex, BSA, and valve anatomy but not AS severity. AA progression rates were low and not influenced by AS severity or valve anatomy.